Strengthening Local Disaster Response in Aceh, North Sumatra, and Padang Through AQRF-Based Occupational Mapping: A Rapid Assessment Study - Heni Jusuf; Lijan Poltak Sinambela (INTERNATIONAL JOURNAL OF ECONOMICS AND MANAGEMENT REVIEW, 2026)
Purpose - Indonesia's vulnerability to disasters necessitates a more structured and competency-based approach to emergency response. This study investigates the application of the ASEAN Qualifications Reference Framework (AQRF) in occupational mapping for disaster management in three high-risk provinces: Aceh, North Sumatra, and Padang. Design/methodology/approach - Using the Rapid Assessment Process (RAP), qualitative data were collected through interviews, document analysis, and field observations. The data were analyzed using the four functional areas of disaster management defined in the AQRF: preparedness, response, recovery, and mitigation. Originality -  his paper contributes to the growing discourse on professionalizing disaster response through structured competency frameworks. It offers localized insights for implementing regional frameworks like AQRF in decentralized disaster governance settings. Findings and Discussion - The study identifies significant institutional gaps in disaster workforce planning, particularly the absence of defined occupational roles and certified competencies. AQRF-based occupational mapping provides a viable model to enhance clarity, coordination, and capacity development in local disaster management agencies. Conclusion - AQRF-based occupational mapping holds significant potential to improve disaster management outcomes in Indonesia’s most vulnerable provinces. Integrating this framework into local policies and training systems can lead to more resilient, responsive, and professionally managed emergency response structures.